Revisiting motives for college student alcohol consumption - Davis, Samuel R., author; Prince, Mark A., advisor; Conner, Bradley T., committee member; Butki, Brian, committee member (Colorado State University. Libraries, 2020)
College students consume alcohol more frequently than the general population. Further, exercise participation is frequently positively associated with alcohol use among college students. While exercise has been consistently demonstrated to be protective in several domains, findings from the alcohol use literature suggest there may be exercise-specific reasons for alcohol use. Our aim was to develop and add a subscale proposed to be measuring the desire to drink to simulate the natural high achieved through exercise to the existing Drinking motives Questionnaire (DMQ). We hypothesized that exercisers drink to simulate more than low exerciser and non-exercisers. This study surveyed college students (N = 1,040) assessing several facets of alcohol use, including the DMQ and 10 proposed simulation motive items. Factor analysis was used to discern the number of latent constructs in the model. Invariance testing was used to assess differences in the simulation factor across no exercise per week (non-exerciser group), below 150 minutes (low exerciser group), and at least 150 minutes (exerciser group). Results indicated a four-factor model best fit the data. The four factors that emerged were enhancement, coping, and social motives, in addition to the added simulation motive. Invariance testing suggested configural invariance, indicating the structure of the simulation construct is the same across exercise groups. Further invariance testing and post-hoc analyses revealed metric and scalar noninvariance indicating differences in levels of endorsement of the simulation motive items. Findings provide preliminary evidence that college students drink for exercise-specific reasons and that the endorsement of these reasons varies across exercise. A new exercise-specific alcohol use motive could help inform more targeted intervention and prevention efforts.